The influence of environmental context in interpersonal observation–execution. Issue 1 (January 2017) - Roberts, James W.; Bennett, Simon J.; Welsh, Timothy N.; Elliott, Digby; Lyons, Jim L.; Hayes, Spencer J.
Cyclical upper-limb movements involuntarily deviate from a primary movement direction when the actor concurrently observes incongruent biological motion. We examined whether environmental context influences such motor interference during interpersonal observation–execution. Participants executed continuous horizontal arm movements while observing congruent horizontal or incongruent curvilinear biological movements with or without the presence of an object positioned as an obstacle or distractor. When participants were observing a curvilinear movement, an object located within the movement space became an obstacle, and, thus, the curvilinear trajectory was essential to reach into horizontal space. When acting as a distractor, or with no object, the curvilinear trajectory was no longer essential. For observing horizontal movements, objects were located at the same relative locations as in the curvilinear movement condition. We found greater involuntary movement deviation when observing curvilinear than horizontal movements. Also, there was an influence of context only when observing horizontal movements, with greater deviation exhibited in the presence of a large obstacle. These findings suggest that the influence of environmental context is underpinned by the (mis-)matching of observed and executed actions as incongruent biological motion is primarily coded via bottom-up sensorimotor processes, whilst the congruent condition incorporates surrounding environmental features to modulate the bottom-up sensorimotor processes.